2008
DOI: 10.1152/ajprenal.00051.2008
|View full text |Cite
|
Sign up to set email alerts
|

Calcitriol blunts the deleterious impact of advanced glycation end products on endothelial cells

Abstract: Advanced glycation end products (AGEs), which are elevated in diabetic and uremic patients, may induce vascular dysfunctions, and calcitriol may improve the cardiovascular complications. Therefore, we examined whether calcitriol may modify the endothelial response to AGEs stimulation. Knowing the importance of nuclear factor-kappaB in endothelial inflammatory responses, the effect of AGEs and calcitriol on this pathway was also studied. Calcitriol was added to endothelial cells previously incubated with AGE-hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
91
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(109 citation statements)
references
References 36 publications
11
91
0
6
Order By: Relevance
“…Some of the included study participants had T2DM and others were uremic patients. Hence, vitamin D acting through VDR may have improved endothelial dysfunction by hindering the damaging effects of advanced glycation end products (which have been reported to be increased in diabetic and uremic patients) by reducing the expression of genes such as IL-6, and IL-8 involved in the advanced glycation end products-activated inflammatory pathway [49].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the included study participants had T2DM and others were uremic patients. Hence, vitamin D acting through VDR may have improved endothelial dysfunction by hindering the damaging effects of advanced glycation end products (which have been reported to be increased in diabetic and uremic patients) by reducing the expression of genes such as IL-6, and IL-8 involved in the advanced glycation end products-activated inflammatory pathway [49].…”
Section: Discussionmentioning
confidence: 99%
“…16 There are also non-calciotropic mechanisms, which may explain the association between vitamin D and arterial stiffness: calcitriol probably directly modulates the vascular smooth muscle cell production 17 and reduces the adverse impact of advanced glycation end-products on vascular aging. 18 There are only few clinical studies dealing with the association between vitamin D and large artery properties, and most of them were done in patients with end-stage renal disease. London et al 19 reported that increased arterial stiffness measured by PWV was significantly associated with vitamin D deficiency in end-stage renal disease patients.…”
Section: Discussionmentioning
confidence: 99%
“…AA 36,37 Finally, calcitriol may also act as a vascular protective agent counteracting the deleterious effects of advanced glycation end products on endothelial function. 38 Increased concentrations of glucose and advanced glycation end products acting through its receptor of advanced glycation end products can induce the expression of proinflammatory molecules by ECs. Calcitriol acting via VDR has been found to decrease the expression of genes involved in advanced glycation end products-activated inflammatory pathway such as RAGE, IL-6, and IL-8 through an NF-κB-mediated mechanism.…”
Section: 34mentioning
confidence: 99%